2010
DOI: 10.1017/s1368980010001631
|View full text |Cite
|
Sign up to set email alerts
|

Status of vitamins A and E in schoolchildren in the centre west of Tunisia: a population-based study

Abstract: Objective: The present study was undertaken to assess the status of vitamins A and E (VA and VE, respectively) and their main determinants in Tunisian children. Design: Cross-sectional population-based study. Setting: Kasserine Governorate in the centre west of Tunisia. Subjects: A total of 7407 children attending the first grade of elementary school were included. VA and VE were assessed by HPLC. Results: The prevalence of moderate VA deficiency (VAD; ,0?70 mmol/l) was 2?3 % and VE deficiency (VED; ,6?97 mmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…A lower vitamin E serum level is positively associated with RRTIs in children, thereby indicating that sufficient vitamin E intake may help prevent the induction of RRTIs in children. The cut-off value suggested that a vitamin E serum level lower than 7.85 mg/L may be a risk factor for RRTIs, whereas vitamin E serum levels higher than the normal value (7 mg/mL) [35, 36] may prevent RRTIs in children.…”
Section: Discussionmentioning
confidence: 99%
“…A lower vitamin E serum level is positively associated with RRTIs in children, thereby indicating that sufficient vitamin E intake may help prevent the induction of RRTIs in children. The cut-off value suggested that a vitamin E serum level lower than 7.85 mg/L may be a risk factor for RRTIs, whereas vitamin E serum levels higher than the normal value (7 mg/mL) [35, 36] may prevent RRTIs in children.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin A deficiency was considered with retinol concentrations <10 μg/dL and low concentrations <20 μg/dL [23]. Vitamin E deficiency was defined with a concentration of alpha-tocopherol <3 μg/mL and low concentrations <5 μg/mL [24]. When using the vitamin E:lipids ratio, vitamin E deficiency was considered with <0.8 mg/g [25].…”
Section: Methodsmentioning
confidence: 99%
“…In a survey of the U.S. population, 26–41% of individuals (depending on ethnicity) had blood plasma αT concentrations at levels that were associated with an increased risk for cardiovascular disease (Ford and Sowell 1999). Although studies of vitamin E sufficiency in developing countries are less widespread and comprehensive, it has been reported that dietary intake and plasma levels of αT were even lower than that in developed countries (Fares et al 2011; Monteiro et al 2009; Oldewage-Theron et al 2010). Given the substantial variation for grain levels of tocopherols (Chander et al 2008; Li et al 2012; Wong et al 2003) and tocotrienols (Weber 1987) among diverse maize lines, it should be possible to exploit this genetic diversity in marker-assisted selection programs that target specific endogenous tocochromanols in maize grain.…”
mentioning
confidence: 99%